OPTIMIZATION OF STARTER IN PRODUCING ANTIBACTERIAL COMPUNDS ISOLATE B.J.T A-6 FROM ANDALEH PLANT (Morus macroura Miq.) - Febrina Anggiastanti; Dwi Hilda Putri (Serambi Biologi, 2020)
Antibacterial resistance has become a serious problem in the health sector, increasing cases of bacterial resistance to antibacterial agents have encouraged researchers to develop and find new bioactive compounds. One source of new bioactive compounds developed is by utilizing endophyte bacteria. B.J.T A-6 isolate is Andaleh endophyte bacteria which has antibacterial activity. This study aims to determine the concentration of the best fermentation starter in producing antibacterial compounds by ATB 10-6 isolates. The B.J.T A-6 isolate in producing the best antibacterial compound was 24 hours fermentation with a starter concentration of 2.5% at 38 hours observation.